Psychobehavioural and Cognitive Adverse Events of Anti-Seizure Medications for the Treatment of Developmental and Epileptic Encephalopathies - Strzelczyk, Adam; Schubert-Bast, Susanne (CNS drugs, 2022)
The developmental and epileptic encephalopathies encompass a group of rare syndromes characterised by severe drug-resistant epilepsy with onset in childhood and significant neurodevelopmental comorbidities. The latter include intellectual disability, developmental delay, behavioural problems including attention-deficit hyperactivity disorder and autism spectrum disorder, psychiatric problems including anxiety and depression, speech impairment and sleep problems. Classical examples of developmental and epileptic encephalopathies include Dravet syndrome, Lennox–Gastaut syndrome and tuberous sclerosis complex. The mainstay of treatment is with multiple anti-seizure medications (ASMs); however, the ASMs themselves can be associated with psychobehavioural adverse events, and effects (negative or positive) on cognition and sleep. We have performed a targeted literature review of ASMs commonly used in the treatment of developmental and epileptic encephalopathies to discuss the latest evidence on their effects on behaviour, mood, cognition, sedation and sleep. The ASMs include valproate (VPA), clobazam, topiramate (TPM), cannabidiol (CBD), fenfluramine (FFA), levetiracetam (LEV), brivaracetam (BRV), zonisamide (ZNS), perampanel (PER), ethosuximide, stiripentol, lamotrigine (LTG), rufinamide, vigabatrin, lacosamide (LCM) and everolimus. Bromide, felbamate and other sodium channel ASMs are discussed briefly. Overall, the current evidence suggest that LEV, PER and to a lesser extent BRV are associated with psychobehavioural adverse events including aggressiveness and irritability; TPM and to a lesser extent ZNS are associated with language impairment and cognitive dulling/memory problems. Patients with a history of behavioural and psychiatric comorbidities may be more at risk of developing psychobehavioural adverse events. Topiramate and ZNS may be associated with negative effects in some aspects of cognition; CBD, FFA, LEV, BRV and LTG may have some positive effects, while the remaining ASMs do not appear to have a detrimental effect. All the ASMs are associated with sedation to a certain extent, which is pronounced during uptitration. Cannabidiol, PER and pregabalin may be associated with improvements in sleep, LTG is associated with insomnia, while VPA, TPM, LEV, ZNS and LCM do not appear to have detrimental effects. There was variability in the extent of evidence for each ASM: for many first-generation and some second-generation ASMs, there is scant documented evidence; however, their extensive use suggests favourable tolerability and safety (e.g. VPA); second-generation and some third-generation ASMs tend to have the most robust evidence documented over several years of use (TPM, LEV, PER, ZNS, BRV), while evidence is still being generated for newer ASMs such as CBD and FFA. Finally, we discuss how a variety of factors can affect mood, behaviour and cognition, and untangling the associations between the effects of the underlying syndrome and those of the ASMs can be challenging. In particular, there is enormous heterogeneity in cognitive, behavioural and developmental impairments that is complex and can change naturally over time; there is a lack of standardised instruments for evaluating these outcomes in developmental and epileptic encephalopathies, with a reliance on subjective evaluations by proxy (caregivers); and treatment regimes are complex involving multiple ASMs as well as other drugs. Graphical Abstract